Impact of Educational Interventions on Acceptance and Uptake of Male Circumcision in the General Population of Western China: A Multicenter Cohort Study. Issue 1 (December 2017) - Zhou, Bo; Ning, Chuanyi; McCann, Chase; Liao, Yanyan; Yang, Xiaobo; Zou, Yunfeng; Jiang, Junjun; Liang, Bingyu; Abdullah, Abu; Qin, Bo; Upur, Halmurat; Zhong, Chaohui; et al.
Abstract To compare different intervention models for promoting male circumcision (MC) to prevent HIV transmission in Western China. A total of 1690 male participants from multiple study sites were cluster randomly allocated to three-stage (Model A), two-stage (Model B), and one-stage (Model C) educational interventions. In all three interventions models, knowledge about MC significantly increased and the reported willingness to accept MC increased to 52.6% (255/485), 67.0% (353/527), and 45.5% (219/481) after intervention, respectively (P < 0.05). Rate of MC surgery uptake was highest (23.7%; 115/485) among those who received Model A intervention, compared to those who received Model B (17.1%; 90/527) or Model C (9.4%; 45/481) interventions (P < 0.05). Multivariable Cox regression analysis identified that Model A or Model B had twice the effect of Model C on MC uptake, with relative risks of 2.4 (95%CI, 1.5–3.8) and 2.2 (95%CI, 1.3–3.6), respectively. Model B was the most effective model for improving participants' willingness to accept MC, while Model A was most successful at increasing uptake of MC surgery. Self-reported attitude towards MC uptake was not strongly correlated with actual behavior in this study focusing on the general male population in Western China.